Determinants of blockchain technology application in primary healthcare delivery: An integrated best-worst approach. Issue 1 (31st December 2023) - Bankuoru Egala, Sulemana; Liang, Decui; Peter Darko, Adjei; Boateng, Dorcas; Yahaya, Haleem
Abstract: Primary healthcare (PHC) has become a concern in most resource constraint economies particularly in the global south where meeting this important economic need has become a burden. Given this, blockchain technology (BT), a promising transformation in contemporary service delivery, has become an alternative for service-oriented institutions to meet their desired goals. In primary healthcare, BT has been utilised to lessen the burden on medical supply chain and data management. Nonetheless, the technology seems to be a preserve of the developed economies. In the global south, not only has the complexities of the technology hindered the implementation of the technology but the understanding of its affordances has also been nascent. This study extends Task-technology fit model with the perceived e-readiness model. Drawing on the best-worst method, this paper investigates PHC managers' decision to embrace BT for PHC delivery in Ghana. The study finds that, in order of relevance, task-technology, infrastructure and individual characteristics are the main drivers of BT adoption and implementation. The study proposes the implementation of various strategies relevant to ensuring a sustainable BT for the management of PHC in resource constraint economies.